Analisis Konseptual Penanaman Nilai-Nilai Tauhid Anak Usia Dini Berdasarkan Pemikiran Al-Ghazali Dan Ibnu Khaldun - Wardati, Laila (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to analyze and synthesize strategies for instilling the values of tauhid (monotheism) in early childhood education based on the thoughts of Al-Ghazali and Ibn Khaldun. Using a qualitative approach through library research, this study examines the primary works of both scholars, such as Ihya’ Ulum al-Din, Ayyuha al-Walad, and Muqaddimah, along with relevant secondary literature. The results reveal that Al-Ghazali emphasizes tauhid education as a process of tazkiyat al-nafs (purification of the soul) and the cultivation of heart-based awareness of God’s oneness through role modeling and habituation. Meanwhile, Ibn Khaldun highlights the social and methodological aspects of education, particularly the principles of tadrīj (gradual learning) and takrīr (repetition). The conceptual synthesis of their ideas results in an integrative strategy for tauhid education consisting of three core pillars: (1) the internalization of tauhid awareness contextualized for early childhood development, (2) gradual and joyful habituation aligned with the child’s developmental stages, and (3) a learning environment grounded in exemplary conduct and social solidarity. This strategy is highly relevant for modern early childhood education institutions as an effort to build children’s faith-based character, moral integrity, and adaptability in the digital age.